Presence of Multiple Genetic Mutations Related to Insecticide Resistance in Chinese Field Samples of Two Phthorimaea Pest Species - Jiang Zhu; Ruipeng Chen; Juan Liu; Weichao Lin; Jiaxin Liang; Ralf Nauen; Suhua Li; Yulin Gao (Insects, 2024)
Potatoes hold the distinction of being the largest non-cereal food crop globally. The application of insecticides has been the most common technology for pest control. The repeated use of synthetic insecticides of the same chemical class and frequent applications have resulted in the emergence of insecticide resistance. Two closely related pests that feed on potato crops are the potato tuber moth, Phthorimaea operculella, and the tomato leafminer, Phthorimaea absoluta (syn. Tuta absoluta). Previous studies indicated the existence of insecticide resistance to various classes of insecticides including organophosphates, carbamates, and pyrethroids in field populations of P. operculella and P. absoluta. However, the exact mechanisms of insecticide resistance in P. operculella and to a lesser extent P. absoluta remain still poorly understood. Detecting resistance genotypes is crucial for the prediction and management of insecticide resistance. In this study, we identified multiple genetic mutations related to insecticide resistance in two species of Phthorimaea. An unexpected genetic divergence on target-site mutations was observed between P. operculella and P. absoluta. Three mutations (A201S, L231V, and F290V) in Ace1 (acetylcholinesterase), four mutations (M918T, L925M, T928I, and L1014F) in VGSC (voltage-gated sodium channel), and one mutation (A301S) in RDL (GABA-gated chloride channel) have been detected with varying frequencies in Chinese P. absoluta field populations. In contrast, P. operculella field populations showed three mutations (F158Y, A201S, and L231V) in Ace1, one mutation (L1014F) in VGSC at a lower frequency, and no mutation in RDL. These findings suggest that pyrethroids, organophosphates, and carbamates are likely to be ineffective in controlling P. absoluta, but not P. operculella. These findings contributed to a deeper understanding of the presence of target-site mutations conferring resistance to commonly used (and cheap) classes of insecticides in two closely related potato pests. It is recommended to consider the resistance status of both pests for the implementation of resistance management strategies in potatoes.